Swimming speed in men’s 100-m freestyle conﬁrms the fairness of the Paralympic Classiﬁcation System: a meta-analysis - Feitosa, Wellington G. (2018)
Despite an increase in popularity of Paralympic sports, there is a lack of studies on these sports, and controversies regarding the classification system for Paralympian swimmers. The Paralympic classification system features 10 classes to provide fair competition for swimmers with a physical disability. The summary of the clean swimming speed (SS) can provide useful information for the classification system in competitive swimming. The aim of this study was to summarize evidence of the fairness of Paralympic categories of male swimmers with a physically disability, focusing on SS in the 100-m front crawl. Multiple databases (PubMed, EMBASE, ISIWeb of Knowledge, SPORTDiscus, Academic Search Premier, CINAHL) were examined for observational studies published until October 2017, on official swimming races. Five studies were found and analyzed (n = 369; national and international level). The random effects model was used for this meta-analysis. Statistical heterogeneity among the studies was assessed by the inconsistency test (I2) and alfa = 0.05. Subgroup analyses were performed with addition of the “class” covariant according to the characteristics of the studies. Bias was analyzed with a forest plot on the OpenMeta[Analyst] software. Increases in SS were related to higher Paralympic classes. Pooling data from all studies and classes, the estimated mean of SS was 1.25 m.s-1, SD = 0.05 m.s-1, p < 0.01, I2 = 99%, p < 0.01. The analysis of sub-groups found high heterogeneity (I2 > 75%, p < 0.05). The results suggest that the Paralympic Classification System seems to be fair for the men’s 100-m freestyle events. Assessment of studies by close classes and by groups with many classes together, e.g. S1 ‒ S10, increased the heterogeneity of the analysis. However, further studies are necessary to explain possible inconsistencies in the Paralympic Classification.